Measuring Anti-Indigenous Attitudes: The Indigenous Resentment Scale - Beauvais, Edana (Race and social problems, 2021)
This paper presents a novel Indigenous resentment scale to measure anti-Indigenous attitudes in settler-colonial societies. I draw from existing quantitative research on measuring outgroup attitudes, Indigenous philosophy, and settler-colonial scholarship to develop a concept and measure of settlers’ resentment toward Indigenous peoples (settlers’ “Indigenous resentment”) with high construct validity. I test the Indigenous resentment scale using original and nationally representative survey data. I conduct a reliability analysis and use statistical learning techniques to show that the Indigenous resentment scale is internally consistent and unidimensional, and has high theoretical construct validity. As I show, the Indigenous resentment scale is a strong predictor of social avoidance behaviors and significantly predicts opposition to government policies designed to help Indigenous peoples. I explain how the Indigenous resentment scale improves upon existing attempts to measure anti-Indigenous attitudes and discuss the usefulness of the scale in social scientific research.